2021
DOI: 10.1155/2021/5510099
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic, Antimicrobial, and Molecular Profiling of Selected Medicinal Plants

Abstract: Natural products have been the center of attraction ever since they were discovered. Among them, plant-based natural products were popular as analgesics, anti-inflammatory, antidiabetic, and cosmetics and possess widespread biotechnological applications. The use of plant products as cosmetics and therapeutics is deep-rooted in Nepalese society. Although there are few ethnobotanical studies conducted, extensive research of these valuable medicinal plants has not been a priority due to the limitation of technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 98 publications
1
10
0
Order By: Relevance
“…The phytochemicals obtained from C. tamala are shown in Table 2 that was compared with the previously reported study and found similar phytochemical profiling [43]. Our findings exhibited that methanolic extracts have the higher TPC and TFC relative to ethanolic extracts as seen in [44]. Phenolics and flavonoids compounds such as quercetin, ferulic acid, anthocyanins, catechin, and resveratrol are the reason behind controlling glycemia via α-glucosidase, αamylase, and lipid peroxidation inhibition, insulin secretion, and accelerating glucose uptake [45,46].…”
Section: Discussionsupporting
confidence: 82%
“…The phytochemicals obtained from C. tamala are shown in Table 2 that was compared with the previously reported study and found similar phytochemical profiling [43]. Our findings exhibited that methanolic extracts have the higher TPC and TFC relative to ethanolic extracts as seen in [44]. Phenolics and flavonoids compounds such as quercetin, ferulic acid, anthocyanins, catechin, and resveratrol are the reason behind controlling glycemia via α-glucosidase, αamylase, and lipid peroxidation inhibition, insulin secretion, and accelerating glucose uptake [45,46].…”
Section: Discussionsupporting
confidence: 82%
“…The production of free radicals at the inflammatory site is one of the major mechanisms of tissue damage produced by several inflammatory disorders [ 11 , 12 ]. Activated neutrophil infiltration to the inflammatory sites is a significant source of proinflammatory mediators and oxygen-derived free radicals, which induces inflammatory reactions [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several human diseases, including cardiac disorders, diabetes, cancer, inflammation, and neurodegenerative diseases, are exacerbated or triggered by oxidative damage to these biological molecules [ 11 ]. Plant-derived natural products, particularly polyphenolics, and related antioxidant phytochemicals have a diverse range of bioactivities, including anti-inflammation, owing to their ability to quench and alleviate oxidative stress in biological systems, thus restoring health [ 12 ]. As a result, the latest research focus has switched towards plant-based natural products as one of the most encouraging sources of curative agents of inflammation and pain [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the percentage yield was calculated using the dry weight of extract and the dry weight of powder soaked in methanol. The secondary extracts were prepared by dissolving the primary extract in water and then fractionated with different solvents such as hexane, dichloromethane, and ethyl acetate based on increased polarity [ 18 ]. The percentage yield was calculated by the given formula: …”
Section: Methodsmentioning
confidence: 99%